Integrated basin modeling - Kite, G.W.; Droogers, Peter (International Water Management Institute, 2000)
River basins are complex areas, combining the natural processes of precipitation, evapotranspiration, surface water and groundwater runoff with man-made features such as dams and reservoirs, diversions and irrigation schemes, and industrial and urban water uses. Computer models may be constructed to represent these natural and man-made processes. Such models are used to help understand processes that are difficult to measure (such as evaporation) and to study the effects of changes in land cover, water management or climate on the natural and man-made processes.